Plant-based biomaterials as scaffolds for cellular agriculture - Woo-Ju Kim; Yoonbin Kim; Reza Ovissipour; Nitin Nitin (Future Foods)
Edible scaffolds are the essential components for cultivated meat. This research aimed to evaluate the performance of food-grade polysaccharides (pectin and alginate) and proteins (soy protein isolate (SPI) and pea protein isolate (PPI)) as scaffolds for cultivated meat production. A myoblast model cell line (C2C12) and an embryonic-derived fish cell line (ZEM2S) were selected as model cell lines. Rheological analysis revealed that the selected gels were viscoelastic solids with shear thinning behavior. The storage modulus (G') and loss modulus (G'') of pectin and PPI were greater than 1000 Pa and 100 Pa. The pectin gels exhibit better structure recovery compared to other biopolymer gels. The texture properties were similar to those of commercial meat analogues. Furthermore, the pectin gels were stable in water. In general, the cytocompatibility of the biomaterial gels was similar for the tested cell lines, except for ZEM2S when exposed to protein gels. Based on the results of mechanical properties and cytocompatibilities of gels, a 3D printed structure with pectin gel was generated. 3D-printed scaffolds promoted the proliferation of C2C12 cells during 5 days of incubation. These findings highlight the potential of plant biomaterials and 3D printing to develop scaffolds for the production of cultivated meat.